Kajian Tindak Tutur Direktif Ayat-Ayat Perintah pada Qur’an ‎Surat Al-Mulk - Mustaka J.P., Angga (Jurnal Studi Al-Qur'an, 2022)
The background of this article departs from the high popularity of Surat al-Mulk. The study of most vital directive speech acts in this study, namely commanding verses and what are the directive speech acts of commands to the verses contained in Surah al-Mulk. Mulk. The research method used is the method of critical discourse analysis of the verses of Q.S. al-Mulk. Data collection techniques used are documents or documentation. The data analysis technique in this article uses Creswell's qualitative data analysis model. The approach used in this study is pragmatic. The results of this study indicate that there are eight directive speech acts in Surah al-Mulk with different functions. Among them is the form of orders to do or not do something, the form of direct orders, and the forms of indirect orders, namely the command of Allah to His servants through the intermediary of the Prophet Muhammad S.A.W.